(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the effects of overcorrection in language classrooms on students’ confidence. Overcorrection, which involves frequently correcting language errors unnecessarily, can interrupt the natural learning process and lower students’ self-esteem and motivation. Through a review of educational theories and practical examples, the article provides insights into fostering a more positive and supportive learning environment. It offers practical tips for educators to balance correcting errors with providing encouragement, creating an atmosphere where students feel confident and empowered to learn from their mistakes.